Language Education as A System: Structure, Functions and Main Components - Tashlanova Nigora Djuraevna (Periodica Journal, 2023)
The sphere of education as a supersystem or a macrosystem includes a set of various educational subsystems, one of which is formed by the system of language education. The system of language education is also heterogeneous. It is a complex hierarchically organized social system created by people, in which people are the main component that determines their purposeful functioning and development. The integrity of the constituent parts, interrelated elements that make up the system of school language education, is ensured, first of all, by its focus on achieving a specific result
Keywords: language education system; communicative principle; principal object of teaching; foreign languages